Analysis of Hospital Disaster Plan Management Implementation Using the Hospital Safety Index - Puspitawaty, Vinna; Muhardi, Muhardi; Aspiranti, Tasya; Adwiyah, Rabiatul; Suwarsi, Sri; Purnamasari, Pupung (Yayasan Gema Bina Nusantara, 2025)
Disasters pose serious threats to communities. Hospital preparedness is therefore essential to ensure effective emergency and disaster response services. This study assesses hospital preparedness using the Hospital Safety Index (HSI), focusing on structural, non-structural, and functional dimensions, and examines disaster management policies at SMC Regional General Hospital (RSUD SMC), Tasikmalaya Regency. A quantitative approach was applied by calculating HSI scores based on standardized indicators from Hospital Disaster Plan Management, covering seven management dimensions and three preparedness standards. The results show that RSUD SMC achieved an overall HSI score of 0.648, placing the hospital in Category A, indicating it is likely to remain operational during emergencies and disasters. Structural preparedness scored 0.822, non-structural preparedness 0.780, and functional preparedness 0.580. Although disaster management has been implemented, it has not been fully optimized, indicating the need for policy revisions and continuous capacity-building to strengthen hospital safety and disaster resilience.